Interlinked and integrated research support services - Ikonen, Arto (Septentrio Conference Series, 2022)
This poster introduces the efficient set of research support services available in University of Jyväskylä’s (JYU) Open Science Centre (OSC). The set includes several essential services for researchers to help them execute an open and responsible research process. The continuous improvement of research support services has led to an interlinked, integrated and harmonious set of technical solutions, processes and workflows which meet the needs of researchers and help them implement open science and FAIR policies in practice. They also save time and enable better working processes for the researchers but also for the experts conducting these services. The poster describes two main services which are interlinked and which both aim to make processes and workflows effortless. One of the main services is when metadata from research information system Converis is utilized using API in the self-archiving process of research articles to the institutional repository. OSC’s experts record the publication metadata on behalf of researchers and the same metadata of the publications is used in the self-archiving process. Also, data harvesting is used to get notification of new publications of researchers affiliated to JYU. Often the researchers don’t even have to inform OSC when their new publication is out. This effortless process combines two different systems (CRIS and institutional repository) and connects workflows regarding them. The poster also introduces a dynamic research data management tool which enables a fluent data management process. The goal of the development of this tool has been to free the researchers of having to learn the use of several different systems. The tool helps the researchers to track the handling process of their data and guides through all the necessary phases of the data management process. Again, the data once recorded is being utilized in other systems and in other phases of the whole process. Both the tool and the data management process it enables are integrated to other systems which are needed for example in storing and sharing the research data.